Hydrazine (N2H4) adsorption on Ni(1 0 0) - Density functional theory investigation - Agusta, Mohammad Kemal (Animo Repository, 2010)
A theoretical study on the structure and adsorption mechanism of hydrazine (N2H4) on Ni(1 0 0) are presented. The hydrazine molecule was found to adsorb on the surface through one of its nitrogen atom in its anti-conformation. The charge transfer from hydrazine lone pair orbitals played a key role in the formation of the bonding. The mechanism involved in the bonding was found to reduce the necessity of hyper-conjugation interaction, that reduces the gauche effect found in hydrazine at the gas-phase. Upon adsorption to the surface, the reduced interaction resulted in the promotion of a more favored conformation through its anti-conformation.